1994
DOI: 10.1159/000176459
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and Treatment of Ascites in Hepatic Cirrhosis

Abstract: In cirrhosis of the liver structural distortion of the sinusoidal vessels is the major factor responsible for the increase in portal venous pressure and the development of abdominal ascites. The mechanisms by which advanced cirrhosis of the liver leads to widespread changes in the systemic circulation including vasodilatation, increased cardiac output and expanded plasma volume, together with activation of a range of antina-triuretic and natriuretic factors, are unclear. Several hypotheses have been proposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Viral hepatitis play an important part in increasing the incidence of LC, as it was shown that in patients with viral hepatitis B and C the chronic pathological process in the liver during the first year can be registered in 15-22.7% of cases [2]. As the course of viral hepatitis B goes on for about 3-5 years -the chronic process is observed in 40.9% of patients and in 74.4% of patients with hepatitis C. It is shown that on average 20-30% of these patients develop liver cirrhosis, and about 20% of the disease is transformed into cancer [2,3,9]. Therefore, adverse environmental conditions, consistently high level of alcoholism, drug addiction growth, reinforced by economic difficulties, promote the growth of the liver disease as well as the diseases in general organs of the gastro-duodenohepatobiliary system, as it is the leader in the maintenance and regulation of homeostasis .…”
mentioning
confidence: 99%
“…Viral hepatitis play an important part in increasing the incidence of LC, as it was shown that in patients with viral hepatitis B and C the chronic pathological process in the liver during the first year can be registered in 15-22.7% of cases [2]. As the course of viral hepatitis B goes on for about 3-5 years -the chronic process is observed in 40.9% of patients and in 74.4% of patients with hepatitis C. It is shown that on average 20-30% of these patients develop liver cirrhosis, and about 20% of the disease is transformed into cancer [2,3,9]. Therefore, adverse environmental conditions, consistently high level of alcoholism, drug addiction growth, reinforced by economic difficulties, promote the growth of the liver disease as well as the diseases in general organs of the gastro-duodenohepatobiliary system, as it is the leader in the maintenance and regulation of homeostasis .…”
mentioning
confidence: 99%